2018
DOI: 10.1177/1354068818787346
|View full text |Cite
|
Sign up to set email alerts
|

Do political parties listen to the(ir) public? Public opinion–party linkage on specific policy issues

Abstract: Political parties are a crucial link between the public and policy outcomes. However, few studies have considered who political parties are responsive to when they take positions on specific policy proposals. This article explores the links between public opinion and the policy positions of political parties on 102 specific policy proposals in Germany using a novel application of multilevel regression with poststratification to estimate the policy preferences of party supporters. While there is a link between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
0
25
0
1
Order By: Relevance
“…Passive "coalitions" in the form of lobbying camps favoring the same policy outcome (Baumgartner et al 2009;Klüver 2013;Mahoney and Baumgartner 2015) can be identified based on gathering the positions of all active actors on an issue. To enable the present study, an online survey was sent to 1,410 active advocates on 50 policy issues as part of the GovLis Project on government responsiveness 2 (Rasmussen, Mäder, and Reher 2018; see also Flöthe and Rasmussen 2019; Junk and Rasmussen 2019; Rasmussen and Reher 2019; Rasmussen, Reher, and Toshkov 2019;Romeijn 2018). Capturing, in addition to these, active cooperation between actors requires collecting even more information, some of which is private, as coalitions do not always leave traces.…”
Section: Method: Capturing Active Lobbying Coalitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive "coalitions" in the form of lobbying camps favoring the same policy outcome (Baumgartner et al 2009;Klüver 2013;Mahoney and Baumgartner 2015) can be identified based on gathering the positions of all active actors on an issue. To enable the present study, an online survey was sent to 1,410 active advocates on 50 policy issues as part of the GovLis Project on government responsiveness 2 (Rasmussen, Mäder, and Reher 2018; see also Flöthe and Rasmussen 2019; Junk and Rasmussen 2019; Rasmussen and Reher 2019; Rasmussen, Reher, and Toshkov 2019;Romeijn 2018). Capturing, in addition to these, active cooperation between actors requires collecting even more information, some of which is private, as coalitions do not always leave traces.…”
Section: Method: Capturing Active Lobbying Coalitionsmentioning
confidence: 99%
“…Capturing, in addition to these, active cooperation between actors requires collecting even more information, some of which is private, as coalitions do not always leave traces. To enable the present study, an online survey was sent to 1,410 active advocates on 50 policy issues as part of the GovLis Project on government responsiveness 2 (Rasmussen, Mäder, and Reher 2018; see also Flöthe and Rasmussen 2019;Junk and Rasmussen 2019;Rasmussen, Reher, and Toshkov 2019;Romeijn 2018). This survey collected information on issue-specific "signaling coalitions," meaning coalitions that jointly campaigned in public or concertedly approached policy makers.…”
Section: Method: Capturing Active Lobbying Coalitionsmentioning
confidence: 99%
“…But there could be advantages of looking into even more concrete party positions on policy issues in order to disentangle the effects of government preferences on policy changes and responsiveness (cf. Romeijn 2018). It is possible that the stronger effects of government preferences on policy change and on responsiveness can be found with more direct measures of party and government preferences.…”
Section: Resultsmentioning
confidence: 99%
“…To address this concern and explore the validity of the policy scale measures, we obtained direct measures of party support or opposition to the subset of 102 cases in Germany (Romeijn 2018). The direct measures were based on hand-coding of the party positions on the basis of statements in the national media.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Some previous research has examined how voter-party congruence varies between different types of parties, with mixed results. Romeijn (2018) studies congruence between public opinion and political parties in Germany. He finds mixed evidence about the extent to which congruence varies between niche parties and mainstream parties, but, if anything, niche parties appear more congruent and more responsive to levels of policy support in the general public.…”
Section: Explaining Variation In Voter-party Proximity Across Issuesmentioning
confidence: 99%